Riding the wave of ependymal cilia: Genetic susceptibility to hydrocephalus in primary ciliary dyskinesia. Issue 9 (17th May 2013) - Lee, Lance
<x xml:space="preserve">Abstract</x> Congenital hydrocephalus is a relatively common and debilitating birth defect with several known physiological causes. Dysfunction of motile cilia on the ependymal cells that line the ventricular surface of the brain can result in hydrocephalus by hindering the proper flow of cerebrospinal fluid. As a result, hydrocephalus can be associated with primary ciliary dyskinesia, a rare pediatric syndrome resulting from defects in ciliary and flagellar motility. Although the prevalence of hydrocephalus in primary ciliary dyskinesia patients is low, it is a common hallmark of the disease in mouse models, suggesting that distinct genetic mechanisms underlie the differences in the development and physiology of human and mouse brains. Mouse models of primary ciliary dyskinesia reveal strain‐specific differences in the appearance and severity of hydrocephalus, indicating the presence of genetic modifiers segregating in inbred strains. These models may provide valuable insight into the genetic mechanisms that regulate susceptibility to hydrocephalus under the conditions of ependymal ciliary dysfunction. © 2013 Wiley Periodicals, Inc.